All-Optical Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Richter, T.; Onishchukov, Georgy; Schubert, C.; Schmauß, Bernhard; Leuchs, Gerd (2014 IEEE Photonics Society Summer Topical Meeting Series, 2014)
Using a cascade of an amplitude and a phase regenerator, multilevel signal processing is demonstrated experimentally for a 25-GBd star-8QAM. Improvements in the signal quality by up to 2 dB are obtaine
lhft_intern.bib::Roethlingshoefer2014_6

All-optical phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Richter, Thomas; Schubert, Colja; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The possibility of all-optical phase-preserving amplitude regeneration for star-8QAM is demonstrated using a modified nonlinear optical loop mirror. Experiments show a reduction in amplitude noise on both amplitude levels simultaneously, considering two different types of signal distortions: deterministic low-frequency amplitude modulation and broadband amplitude noise. Furthermore, using this amplitude regeneration, the robustness against nonlinear phase noise from fiber nonlinearity in a transmission line is increased. The scheme suppresses the conversion of amplitude noise to nonlinear phase noise. This is shown for simultaneous amplitude regeneration of the two amplitude states as well as for amplitude regeneration of the high-power states only. If the transmission is limited by nonlinear phase noise, single-level operation at the more critical higher-power state will benefit because of the wider plateau region. Numerical simulations confirm the experimental result

All-optical signal regeneration of advanced modulation formats - Röthlingshöfer, Tobias; Richter, Thomas; Stiller, Birgit; Onishchukov, Georgy; Schubert, Colja; Schmauß, Bernhard; Leuchs, Gerd (Nonlinear Frequency Generation and Conversion: Materials, Devices, and Applications XIII, 2014)
With growing demand on transmission capacity, spectral-efficient multilevel modulation formats such as quadrature amplitude modulation (QAM) become of great interest. One of their weaknesses is high sensitivity to noise accumulation, especially in long-haul transmission systems. Our investigations have shown the possibility of all-optical regeneration of multiple amplitude and phase states. Processing of amplitude noise in several amplitude states is based on periodicity of interference conditions in modified nonlinear fiber Sagnac interferometers. Their staircase-like power transfer characteristic can be used for phase-preserving amplitude regeneration of multiple amplitude states. Processing of QAM with up to three non-zero amplitude states, e.g. 16QAM, has been demonstrated in numerical simulations. Furthermore, simultaneous amplitude regeneration of a star-8QAM format with two amplitude states was performed experimentally. Recently, it has also been shown that phase-sensitive amplification for multiple phase states can be realized in fiber optical parametric amplifiers using four-wave mixing (FWM) with a high-order idler. Our numerical simulations and experimental results for star-8QAM revealed that with some modifications, this approach can be used not only for reduction of phase noise in multilevel phase-shift keying but also for signals with multiple amplitude states. The transmission improvement using a cascade of these two regenerator types has been demonstrated in numerical simulations and experiments. Numerical investigations confirm also the possibility to combine both approaches in a single device by using the highly nonlinear fiber in the Sagnac interferometer loop simultaneously for phase-sensitive amplification in one propagation direction. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use onl
lhft_intern.bib::Roethlingshoefer2014_8

All-Optical Simultaneous Multilevel Amplitude and Phase Regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE Photonics Technology Letters, 2014)
Simultaneous amplitude and phase noise reduction of multiple signal states using a nonlinear amplifying loop mirror with integrated directional phase-sensitive amplifier are presented for the star-eight quadrature amplitude modulation transmission format as an example. The performance of this combined regenerator scheme is compared with that of a cascade of separate phase and amplitude regenerators. It could be shown that an improvement in the error vector magnitude of 4 dB for the high-power states with simultaneous improvement of 5 dB for the low-power states is possible in both cases. Transmission improvement by regeneration is considered for two noise types: 1) amplified spontaneous emission and 2) nonlinear phase noise. Both schemes can either improve the bit error rate by an order of magnitude or enable an increase of the fiber launch power by 3 d
lhft_intern.bib::Roethlingshoefer2014a

Cascaded phase-preserving multilevel amplitude regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optics Express, 2014)
The performance of cascaded in-line phase-preserving amplitude regeneration using nonlinear amplifying loop mirrors has been studied in numerical simulations. As an example of a spectrally efficient modulation format with two amplitude states and multiple phase states, the regeneration performance of a star-16QAM format, basically an 8PSK format with two amplitude levels, was evaluated. An increased robustness against amplified spontaneous emission and nonlinear phase noise was observed resulting in a significantly increased transmission distance.
lhft_intern.bib::Roethlingshoefer2014_4

Influence of group-velocity dispersion on multilevel phase-preserving amplitude regeneration in a nonlinear amplifying loop mirror - Röthlingshöfer, Tobias; Toth, Daniel; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
Numerical simulations have shown a significant influence of group-velocity dispersion (GVD) of the highly nonlinear fiber on the transfer characteristics of a nonlinear amplifying loop mirror (NALM). The effect is especially strong for the anomalous dispersion regime where an interaction of GVD and self-phase modulation (SPM) leads to formation of high-order solitons. The irregularities of the resulting NALM transfer functions can be used for phase-preserving amplitude regeneration of several, irregular-spaced amplitude states for multi-level modulation formats. The regeneration performance was estimated for a 16QAM signal with three amplitude states where a reduction of amplitude noise without significant signal phase distortions has been observe
lhft_intern.bib::Roethlingshoefer2012ca

Multilevel amplitude and phase regeneration in a nonlinear amplifying loop mirror with a phase-sensitive amplifier - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Transparent Optical Networks (ICTON), 2012)
A novel regenerator scheme for all-optical multilevel simultaneous amplitude and phase noise suppression is proposed. For a star-8QAM signal, consisting of two amplitude and four phase states, EVM reduction is 4 dB and 2.5 dB for the high- and low-power states, respectively. The limiting effects of the regenerator performance have been considered.
lhft_intern.bib::Roethlingshoefer2012cb

Optimization of Dispersion-Imbalanced Loop Mirror for Phase-Preserving Amplitude Regeneration - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (IEEE/LEOS Winter Topicals Meeting Series, 2009)
The adaptation and optimization of a dispersionimbalance loop mirror for phase-preserving amplitude 2R regeneration is shown by numerical simulations. Its performance has been evaluated for DPSK transmission. A 4.8dB Q-factor improvement has been demonstrated.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.optimi

Performance analysis of simultaneous multilevel amplitude and phase regeneration - Röthlingshöfer, Tobias; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (39th European Conference and Exhibition on Optical Communication (ECOC), 2013)
A star-8QAM regeneration was investigated in numerical simulations for two schemes: a combined NALM with a PSA in the loop and a cascade of PSA and NALM. Significant improvements in error vector magnitude and bit error rate are achieved for both schemes in a transmission system limited by amplified spontaneous emission and nonlinear phase noise.
lhft_intern.bib::Roethlingshoefer2013a

Phase-preserving amplitude regeneration of a two-amplitude-level modulation format - Röthlingshöfer, Tobias; Richter, Thomas; Schubert, Colja; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Conference on Lasers and Electro-Optics Pacific Rim, 2013)
It has been experimentally shown that a modified nonlinear loop mirror can be used for all-optical star8-QAM processing. An amplitude noise reduction of 2.2 dB could be demonstrated for the high-power state
lhft_intern.bib::Roethlingshoefer2013b

Phase-Preserving Amplitude Regeneration Using Dispersion-Imbalanced Loop Mirror - Röthlingshöfer, Tobias; Sponsel, Klaus; Stephan, Christian; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (Optical Fiber Communication 2009, 2009)
Scheme and parameters of dispersion-imbalance loop mirror (DILM) have been optimized for phase-preserving amplitude 2R regeneration. DILM performance for DPSK transmission has been evaluated in numerical simulations. A 4.8 dB Q-factor improvement has been demonstrated. © 2009 OSA.
UnivIS-Import:2017-12-18:Pub.2009.tech.IE.LEH.phasep
Keywords: (060.4370) Nonlinear optics; fibers; (060.5060) Phase modulation

Reduction of the Rayleigh-Backscattering Impact in Nonlinear Loop Mirrors by Dispersion Management - Röthlingshöfer, Tobias; Sponsel, Klaus; Onishchukov, Georgy; Schmauß, Bernhard; Leuchs, Gerd (OSA Conference on Nonlinear Photonic, 2010)
UnivIS-Import:2016-06-01:Pub.2011.tech.IE.LEH.reduct